Constructing Electronic Phase Diagram for the Half-filled Hubbard Model with Disorder - Tuan, Hoang Anh; Hai Yen, Nguyen Thi (Communications in Physics, 2018)
The electronic phase diagram of strongly correlated systems with disorder is constructed using the typical-medium theory. For half-filled system, the combination of the linearized dynamical mean field theory and equation of motion approach allows to derive the explicit equations determining the boundary between the correlated metal, Mott insulator, and Anderson insulator phases. Our phase diagram is consistent with those obtained by the more sophisticated methods